Hate in Word and Deed: The Temporal Association Between Online and Offline Islamophobia - Wiedlitzka, Susann (Journal of quantitative criminology, 2023)
Objectives The aim of the present study is to explore whether there is a temporal association between anti-Islamic online and offline hate, and if so in which direction. Methods We used data on hateful Twitter content, and hate incidents and hate crimes/offences recorded by the Metropolitan Police Service in the United Kingdom to analyse this association, using time-series analysis. This study is unique in its use of newly developed technology to undertake big data analysis with recent, disaggregated online and offline hate data. Results Our study examined the ‘everyday’ incidents of (online and offline) hate that affect communities throughout the United Kingdom and we found that anti-Islamic hate speech followed rather than preceded Islamophobic hate offline. Conclusions Our findings likely point to what we have referred to as compound retaliation , which suggests that media and social media dissemination about offline acts of hate compound already tense intergroup hostilities, providing further permission for those to express hatred online. Such a situation represents the compounding of hate and hostility through offline and online networks that are likely to be reinforcing.